Using genomic DNA copies to enumerate Mycobacterium tuberculosis load in macaque tissue samples. (July 2021) - Willemse, Danicke; Kaushal, Deepak
Abstract: It is important to accurately quantify Mycobacterium tuberculosis ( Mtb ) load in laboratory-based tuberculosis (TB) research. This study aims to determine if real-time quantitative PCR (qPCR) and digital PCR (dPCR) can be used instead of colony forming unit (CFU) enumeration, to quantify Mtb load in rhesus and cynomolgus macaque tissue samples. Tissue samples of actively infected high Mtb- burden rhesus and cynomolgus macaques were selected from historic sample collections. CFUs were enumerated by plating, and Chelex-extracted genomic DNA used to quantify bacterial load by qPCR and dPCR. Three genes, sigA, 16S and CFP10, were assessed for their ability to quantify Mtb . All genes showed comparable quantification of Mtb between 2 and 20 000 copies/μl in the qPCR and 5–4000 copies/μl in the dPCR assay. The highest bacterial load was observed with dPCR, followed by qPCR, and CFU enumeration. Although the CFU count was consistently lower than the genomic copy numbers predicted by qPCR and dPCR, a significant correlation was observed. Quantification of Mtb by PCR was, however, only possible in higher- Mtb- load samples, suggesting that qPCR and dPCR quantification assays can predict bacterial load in actively infected and higher- Mtb- burden macaque tissue samples.